2011
DOI: 10.3109/13880209.2011.596210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ether- and water-soluble fractions ofCarica papayaethanol extract in experimentally induced hyperlipidemia in rats

Abstract: The anti-hyperlipidemic effect was evaluated in olive oil-loaded rats. Acute treatment caused stimulatory effect on HDL level and inhibition in TC and TG elevation induced by olive oil. The extract and water fraction showed protective action by increasing the HDL cholesterol level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Traditionally, different parts of the papaya plant are used in the treatment of various ailments such as asthma, ulcers, eczema, diabetes, helminth infections and fever (Nguyen et al 2013). Research also demonstrated its beneficial traditional role in wound healing, and in the treatment of cardiovascular diseases, dengue fever, cancer, malaria, hypoglycemia, hyperlipidemia, fungal diseases and as a male contraceptive (Gupta et al 1990;Nayak et al 2007;Goyal et al 2010;Otsuki et al 2010;Iyer et al 2011;Pedro et al 2011;Kovendan et al 2012;Yasmeen & Prabhu 2012;Nunes et al 2013). Papaya extracts have also been reported to have significant anti-inflammatory activity (Owoyele et al 2008;Lee et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, different parts of the papaya plant are used in the treatment of various ailments such as asthma, ulcers, eczema, diabetes, helminth infections and fever (Nguyen et al 2013). Research also demonstrated its beneficial traditional role in wound healing, and in the treatment of cardiovascular diseases, dengue fever, cancer, malaria, hypoglycemia, hyperlipidemia, fungal diseases and as a male contraceptive (Gupta et al 1990;Nayak et al 2007;Goyal et al 2010;Otsuki et al 2010;Iyer et al 2011;Pedro et al 2011;Kovendan et al 2012;Yasmeen & Prabhu 2012;Nunes et al 2013). Papaya extracts have also been reported to have significant anti-inflammatory activity (Owoyele et al 2008;Lee et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this concern, previous studies revealed that water extract of papaya fruits contains significant amounts of α-tocopherol (Ching and Mohamed, 2001), benzylisothiocyanate (Basu and Haldar, 2008), alkaloids such as carpasemine and carpain (Iyer et al, 2011), lycopene (van A photo micrograph in kidney tissue of (A) control rat showing the normal density of total protein in renal tubular epithelial cells manifested by the blue color reaction, (B) rats treated with WE showing the normal distribution of bromophenol blue reaction, (C) rats treated with EE showing normal distribution of bromophenol blue reaction in different renal tissues, (D) rats fed OTA-contaminated diet showing the distribution of protein reaction in renal tubules, renal corpuscles and the hyaline casts revealed weak reaction in some tubules (arrow) and mild reaction in the glomruler tufts, (E) rats fed OTA-contaminated diet and treated wit WE showing strong reaction in the renal tubules (inset) and a moderate reaction in the glomeruli and (F) rats fed OTA-contaminated diet and treated with EE showing a moderate reaction in the renal tubules have moderate reaction and mild reaction in the glomeruli. Breemen and Pajkovic, 2008), proteolytic enzymes such as chymopapain and papain (Seigler et al, 2002), cystatin, ascorbic acid, cyanogenic glucosides and glucosinolates (Seigler et al, 2002), triterpenes, organic acids (Cowan, 1989;Osuna-Torres et al, 2005), as well as flavonoids (Miean and Mohamed, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…After 30 min at room temperature, the absorbance was measured at 765 nm using V-530 UV/visible spectrophotometer. Estimation of phenolic compounds as catechin equivalents was carried out using standard curve of catechin (Jayaprakasha et al, 2003).…”
Section: Determination Of Total Phenolic Compoundsmentioning
confidence: 99%
“…Papaya contains alpha-tocopherol, lycopene, benzylisothiocynate, proteolytic enzymes such a papain and chymopapain [73][74][75][76]. The phytochemical constituent of papaya contains various forms of alkaloids; carpain and carpasemine [77], triterpenes, organic acids [78,79]. Moreover, they also have cystatin, ascorbic acid, cyanogenic glucosides and glucosinolates [80] phenols [38] and flavonoids [80].…”
Section: Alternative and Complimentary Management Of Mycotoxicosis Hementioning
confidence: 99%